Global approach of mean service satisfaction assessment. Issue 1 (14th January 2014) - Kora, Ahmed Dooguy; CISSE, Ibrahima; Cances, Jean‐Pierre
Abstract : A theoretical expression for mobile service satisfaction assessment has been proposed. Mobile networks users' satisfaction is a major concern for the operators and regulators. Therefore a certain level of network qualification is required to be offered to consumers by operators thanks to the decisions initiated by the regulation authority. For the assessment of the level of satisfaction, several methodologies and tools (measuring and monitoring) have emerged. Ranking in two broad categories, namely the objective and subjective methods, both have advantages as well as disadvantages. This Letter has proposed a unified approach to evaluate more objectively users' level of satisfaction of a service based on the most common network key performance indicators (KPIs) rate following the different methods. This approach's main advantage is that it has taken advantages of the different positive aspects of the existing methods and outperformed their limitations thanks to the introduced concept of global KPI. In addition, the size of samples according to each method has been considered. A mean service satisfaction theoretical expression has been proposed to regulation authority, consumers association and operators as common base of service satisfaction assessment.